On the Security of Secure Server-Designation Public Key Encryption with Keyword Search. (19th July 2018) - Lin, Xi-Jun; Sun, Lin; Qu, Haipeng; Liu, Dongxiao
Abstract: Recently, a new framework, called secure server-designation public key encryption with keyword search (SPEKS), was proposed by Chen to withstand online keyword guessing attack. Moreover, Chen proposed a concrete scheme (IBE, TE)-2-SPEKS and proved that their scheme meets trapdoor indistinguishability. In this comment, we point out that the trapdoor, in fact, can be distinguished by the adversary.